PENGARUH KARAKTERISTIK KOMITE AUDIT DAN FUNGSI AUDIT INTERNAL TERHADAP PRAKTIK MANAJEMEN LABA RILL - Muhammad Haikal Al Hafizh (2022)
This study is quantitative research and aims to analyze the significant effect of audit committee characteristics and internal audit function on real earnings management practices in non financial companies listed on the Indonesia Stock Exchange for the 2018-2020 period. This study also uses control variables, namely profitability, leverage, and firm size. Real earnings management as the dependent variable is proceeded by Cohen et al (2008) model. The characteristic of the audit committee is proxied by size, expertise, duality role, and attendance meetings. Meanwhile, internal audit function is proxied by size, expertise, and certified. This study uses a sample of 519 listed Indonesian firms (non financial) covering the period 2018 to 2020 was used for this study. The analysis method used is panel data regression with STATA version 14. The results of this study prove that expertise and meeting attendance of audit committee also size and expertise of internal audit have a negative and significant effect on real earnings management. Meanwhile, duality role of audit committee and certification of internal audit have a positive and significant effect on real earnings management. However, size of audit committee has no significant effect on real earnings management,